The small molecule SERCA activator CDN1163 increases energy metabolism in human skeletal muscle cells - Abel M. Mengeste; Jenny Lund; Parmeshwar Katare; Roya Ghobadi; Hege G. Bakke; Per Kristian Lunde; Lars Eide; Gavin O' Mahony; Sven Göpel; Xiao-Rong Peng; Eili Tranheim Kase; G. Hege Thoresen; et al. (Elsevier, 2021)
Background and objective: A number of studies have highlighted muscle-specific mechanisms of thermogenesis involving futile cycling of Ca2+ driven by sarco (endo)plasmic reticulum Ca2+-ATPase (SERCA) and generating heat from ATP hydrolysis to be a promising strategy to counteract obesity and metabolic dysfunction. However, to the best of our knowledge, no experimental studies concerning the metabolic effects of pharmacologically targeting SERCA in human skeletal muscle cells have been reported. Thus, in the present study, we aimed to explore the effects of SERCA-activating compound, CDN1163, on energy metabolism in differentiated human skeletal muscle cells (myotubes). Methods: In this study, we used primary myotube cultures derived from muscle biopsies of the musculus vastus lateralis and musculi interspinales from lean, healthy male donors. Energy metabolism in myotubes was studied using radioactive substrates. Oxygen consumption rate was assessed with the Seahorse XF24 bioanalyzer, whereas metabolic genes and protein expressions were determined by qPCR and immunoblotting, respectively. Results: Both acute (4 ​h) and chronic (5 days) treatment of myotubes with CDN1163 showed increased uptake and oxidation of glucose, as well as complete fatty acid oxidation in the presence of carbonyl cyanide 4-(trifluromethoxy)phenylhydrazone (FCCP). These effects were supported by measurement of oxygen consumption rate, in which the oxidative spare capacity and maximal respiration were enhanced after CDN1163-treatment. In addition, chronic treatment with CDN1163 improved cellular uptake of oleic acid (OA) and fatty acid β-oxidation. The increased OA metabolism was accompanied by enhanced mRNA-expression of carnitine palmitoyl transferase (CPT) 1B, pyruvate dehydrogenase kinase (PDK) 4, as well as increased AMP-activated protein kinase (AMPK)Thr172 phosphorylation. Moreover, following chronic CDN1163 treatment, the expression levels of stearoyl-CoA desaturase (SCD) 1 was decreased together with de novo lipogenesis from acetic acid and formation of diacylglycerol (DAG) from OA. Conclusion: Altogether, these results suggest that SERCA activation by CDN1163 enhances energy metabolism in human myotubes, which might be favourable in relation to disorders that are related to metabolic dysfunction such as obesity and type 2 diabetes mellitus.